1996
DOI: 10.1029/96ja02601
|View full text |Cite
|
Sign up to set email alerts
|

On the origins of the upward shift of elevated (bimodal) ion conics in velocity space

Abstract: We present a statistical study of elevated (bimodal) ion conics observed by the Exos D (Akebono) satellite from 0900 to 1500 magnetic local time (MLT). We especially focus on a comparative analysis of elevated conics with standard conics and ion beams. Elevated conics are observed mainly above 6,000 km, while standard conics begin to appear at lower altitudes. The energy of elevated conics is usually higher than that of standard ion conics. This is consistent with the idea that the elevated conics evolve from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…That would seem to allow for greatly varying acceleration rates as well as broad ion pitch angle distributions. In fact, it is a vision that has been prompted by the frequent observations over the last 30 years of transversely accelerated ions, and it is one that is specifically consistent, superficially at least, with published statistics on the altitude dependence of ''conical'' ion velocity distributions [e.g., Peterson et al, 1992;Miyake et al, 1993Miyake et al, , 1996. However, a smoothly progressing form of acceleration alone cannot explain the occasional observation [Lennartsson, 2003] of azimuthally collimated and monoenergetic keV O + ions at 90°pitch angle at high altitude (R $ 6 R E ).…”
Section: Discussionmentioning
confidence: 82%
“…That would seem to allow for greatly varying acceleration rates as well as broad ion pitch angle distributions. In fact, it is a vision that has been prompted by the frequent observations over the last 30 years of transversely accelerated ions, and it is one that is specifically consistent, superficially at least, with published statistics on the altitude dependence of ''conical'' ion velocity distributions [e.g., Peterson et al, 1992;Miyake et al, 1993Miyake et al, , 1996. However, a smoothly progressing form of acceleration alone cannot explain the occasional observation [Lennartsson, 2003] of azimuthally collimated and monoenergetic keV O + ions at 90°pitch angle at high altitude (R $ 6 R E ).…”
Section: Discussionmentioning
confidence: 82%
“…Regardless of what other processes are involved, the escape of heavy ions from Earth's gravity undoubtedly requires either parallel acceleration or perpendicular heating to gain the 10 eV or more of energy needed. In the low-altitude region pertinent to this study (_< 4000 km), conic distributions dominate over beams [Gorney et al, 1981;Miyake et al, 1996], so that perpendicular heating is the most important process. Recent statistical studies using Freja data at 1700 km ] and Fast Auroral Snapshot (FAST) data between 2000 and 4000 km [Lund et al, 2000] suggest that broadband extremely low frequency (BBELF) waves are the dominant heating agent in this region, eclipsing electromagnetic ion cyclotron waves and lower hybrid waves.…”
mentioning
confidence: 99%
“…The energy reaches the maximum when the conic angle is decreased to about 60 . Miyake et al (1996) showed that the ion conics with conic angles near 60 are statistically most energetic. This is explained by the extended energization region along the orbit of conic ions.…”
Section: Observationsmentioning
confidence: 99%
“…There have been several reports on occurrence frequencies of ion conics based on satellite observations (Gorney et al, 1981;Yau et al, 1984;Kondo et al, 1990;Thelin et al, 1990;Peterson et al, 1992;Miyake et al, 1993Miyake et al, , 1996. Most of them, however, did not examine the quantitative relationship of the observed occurrences between ion conics with di erent conic angles and at di erent altitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation